Role of the functional status of the autonomic nervous system in the clinical course of purulent meningitis - D. A. Zadiraka; O. V. Ryabokon (Zaporozhye State Medical University, 2014)
Purulent meningitis is defined by high indices of sickness and lethality rates, a great risk of cerebral and extracerebral complications development, steady residual consequences formation. During neuroinfections, the state of adaptation mechanisms, which is characterized by exhaustion of regulatory systems with the development of decompensation, plays a crucial part. Heart rate variability clearly reflects the degree of regulatory system tension caused by the influence of both physiological and pathological factors. Research aim: to increase the autonomic dysfunction diagnostics efficiency for patients suffering from purulent meningitis in the disease dynamics based on the complex of clinical evidence and functional status of autonomic nervous system. Materials and methods. There were 60 patients with purulent meningitis under medical observation. Wein's questionnaire was used for the detection of clinical presentations of autonomic dysfunction. Functional status of autonomic nervous system was diagnosed using the method of computer-based cardiointervalometry. The screening group was formed of 20 healthy individuals. Research findings and theirs discussion. Cerebral meningeal symptom was dominant among the patients suffering from purulent meningitis at the peak of the disease. At hospitalization every fifth person (23,3%) had the objective evidence of autonomic dysfunction in the form of a postural tremor of upper limbs and eyelids. The analysis of autonomic nervous system parameters functional status among the patients suffering from purulent meningitis at the peak of disease showed heart rate variability decrease in the main branches of autonomic regulation and the presence of autonomic imbalance towards vagotonia. Since the second week, clinical signs of autonomic dysfunction prevailed in the dynamics of patients suffering from purulent meningitis in the course of standard treatment, which was proved by Wein's survey of the patients. The predominance of the autonomic dysfunction signs in the clinical picture was combined with the prolonged decreasing rating of humoral effects' spectrum (p<0,04) against the background of other stably changed heart rate variability parameters. In the course of standard treatment a certain regress of autonomic dysfunction symptoms was stated among the patients suffering from purulent meningitis, the evidence of which was the decreasing score (р<0,00001) according to Wein's questionnaire in comparison with the previous data. At the moment of dismissal from hospital most patients (72,7%) had, however, both visual and clinical signs of autonomic disorders. The functional status of autonomic nervous system among the patients suffering from purulent meningitis at the period of reconvalescence was characterized by low rate of heart rate variability spectral parameters combined with the autonomic imbalance towards vagotonia. SUMMARY 1. The predominance of cerebral meningeal symptom among the patients suffering from purulent meningitis at the peak of the disease is combined with individual visual signs of autonomic dysfunction in the form of eyelids and upper limbs postural tremor and heart rate variability lowering rate with the presence of autonomic imbalance towards vagotonia. 2. Since the second week, clinical signs of autonomic dysfunction prevailed in the dynamics of patients suffering from purulent meningitis in the course of standard treatment, which was combined with the prolonged decreasing rating of humoral effects' spectrum (p<0,04) against the background of other stably changed parameters of heart rate variability. 3. The period of reconvalescence among the patients suffering from purulent meningitis is characterized by the retention of autonomic disorders clinical signs among 72,7% of patients and low intensity of heart rate variability with the presence of autonomic imbalance towards vagotonia.